A bi-metallic MOF catalyst via sensitive detection & adsorption of Fe3+ ions for size-selective reaction prompting. Issue 28 (23rd May 2018) - Li, Yang; Chang, Ziling; Huang, Fangmin; Wu, Pengyan; Chu, Huacong; Wang, Jian
Abstract : Novel MOF adsorbed Fe 3+ presents the first example of a bi-metallic Lewis-acid catalyst for the cyanosilylation reaction in a size-selective fashion. Abstract : A cadmium(ii )-based MOF, Cd-MDIP, was successfully prepared by hydrothermal reaction between the tetra-carboxylic ligand 5, 5′-methylenebisophthalic acid (H4 MDIP) and cadmium perchlorate. The X-ray crystal structure analysis showed that there are two uncoordinated carboxyl groups in each ligand and a 1D elliptical channel along the [001] direction. Because of the existence of uncoordinated carboxyl groups within open frameworks, Cd-MDIP exhibited a high sensitivity (Stern–Volmer constant K SV = 4.13 × 10 4 L mol −1 ) and a low detection limit (80 nM) for Fe 3+ ions in pure water, which is much lower than the national standard for Fe 3+ in daily drinking water (5.4 μM) set by the Ministry of Environmental Protection of P. R. China. Most importantly, Cd-MDIP also featured the ultrahigh adsorption of Fe 3+ in aqueous solution that cannot be destroyed even by EDTA/base. Importantly, the MOF material (Cd-MDIP⊃Fe 3+ ) after adsorbing Fe 3+ could act as the first example of an excellent bi-metallic Lewis-acid catalyst for the cyanosilylation reaction of aromatic aldehydes in a size-selective fashion, and its efficiency was almost 10-times higher than that of the original Cd-MDIP.